POLÍCIA FEDERAL E COMBATE À CORRUPÇÃO: estudo de caso do Estado do Maranhão em tempos de pandemia de covid-19 - BORBA, Rodrigo Rosa (2024)
The present study problematizes the factors contributing to the practice of crimes related to corruption in the State of Maranhão during the covid-19 pandemic, based on the analysis of police investigations launched and police operations launched by the Federal Police in the federative unit. To this end, we initially examine the criminological factors that contributed to these crimes to understand their nuances. Subsequently, we identify effective measures for controlling corruption based on the experience of nations that have been successful in this objective. Finally, the legal factors that contributed to the practice of crimes related to corruption involving the misuse of federal funds intended to combat the pandemic caused by the SARS-CoV-2 virus are analyzed, presenting data from police investigations launched and operations judicial police launched by the Federal Police in Maranhão. In this sense, the research is based on a legal-descriptive study that employs the inductive approach, together with critical and dialectical socio-legal methods, and bibliographic and documentary research techniques. As a result, the hypothesis is supported that the corruption crimes allegedly committed in Maranhão during the COVID-19 pandemic resulted from differential associations structured around different interests, verified through the study of white-collar crime, from the perspective of the Theory of Differential Association and Critical Criminology – which constitute the theoretical framework of this study –, and were driven by the relaxation of public contracting controls during the pandemic period and by the inconsistencies of the Brazilian Punitive System for combating corruption.